Pelatihan Aplikasi Perpustakaan Digital pada Siswa MAS Darrul Mukarram - Sidiq, Abdurrahim; Raharjo, Mokhamamad Ramdhani; Trinizaa, Ice; Agustini, Dian; Faridha, Mutia (Universitas Pahlawan Tuanku Tambusai, 2025)
In the 4.0 era, the ability to use information technology tools is essential because almost all fields today cannot escape using information technology to support activities. MAS Darul Mukarram is one of the schools that applies information technology as a learning support, namely the use of digital library applications to support student literacy, There are still obstacles faced in the field, and some students have difficulty using the application. Based on these problems, the solution that will be implemented is in the form of training on the use of digital library applications for students. As a result of this service activity, participants experienced an increase in their understanding of using digital library applications as a learning support medium such as reading books online and the process of borrowing and returning books online, besides indirectly increasing students' reading interest.